Strength of optical glass under conditions of axial compression - Okhrimenko, G.M.; Rodichev, Yu.M.; Maslov, V.P. (Проблемы прочности, 1985)
We studied optical glass types LK5, K8, TK3, TKII4 belonging to the group of crown glasses (containing lead oxide PbO < 3%), and FI, FI01, TFI01, TFI0 belonging to the group of flint glasses (containing lead oxide PbO > 3%).